Using the movement patterns of reintroduced animals to improve reintroduction success. Issue 4 (1st August 2014) - Berger-TAL, Oded; Saltz, David
Abstract: Despite their importance to conservation, reintroductions are still a risky endeavor and tend to fail, highlighting the need for more efficient post-release monitoring techniques. Reintroduced animals are released into unfamiliar novel environments and must explore their surroundings to gain knowledge in order to survive. According to theory, knowledge gain should be followed by subsequent changes to the animal's movement behavior, making movement behavior an excellent indicator of reintroduction progress. We aim to conceptually describe a logical process that will enable the inclusion of behavior (in particular, movement behavior) in management decision-making post-reintroductions, and to do so, we provide four basic components that a manager should look for in the behaviors of released animals. The suggested components are release-site fidelity, recurring locations, proximity to other individuals, and individual variation in movement behavior. These components are by no means the only possible ones available to a manager, but they provide an efficient tool to understanding animals' decision-making based on ecological theory; namely, the exploration-exploitation trade-off that released animals go through, and which underlies their behavior. We demonstrate our conceptual approach using data from two ungulate species reintroduced in Israel: the Persian fallow deer Dama mesopotamica and the Arabian oryx Oryx leucoryx [ Current Zoology 60 (4): 515–526, 2014].